INOVASI PEMBELAJARAN IPA: PENGARUH MEDIA EXPLOSION BOX TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 1 LUWE HULU - Ririn Maharani; Setria Utama Rizal; Sulistyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research endeavors to examine the impact of employing Explosion Box learning media on enhancing student learning achievements in Natural Science (IPA) subjects on energy sources in class IV SDN 1 Luwe Hulu. The rationale for this study stems from the limited student engagement and learning achievements attributed to the application of traditional, less interactive pedagogical approaches. The research methodology employed a pre-experimental framework with a quantitative orientation, utilizing a one-group pre-test and post-test design. The sample consisted of 22 students, and data was collected through observation and multiple choice tests. The statistical analysis outcomes, derived from the Wilcoxon Signed Ranks test, demonstrated a notable improvement in learning achievements, indicated by a significance level of <0.001. The average student score increased from 49.59 (pretest) to 94.77 (posttest). The percentage of learning implementation reached 90.22%, which shows that Explosion Box media is effective in creating interactive and meaningful learning. These findings indicate that the Explosion Box is able to increase students' motivation, engagement, and understanding, and is recommended as an innovative media in science learning at the elementary school level.